Analisis Persebaran Panas Pada Mesin Oven Pengering Kerupuk Dengan Burner Sederhana Berbasis Computational Fluid Dynamics - Adetia Riski Wardana; Mukhtar, Agus; Burhanuddin, Aan (Journal of Applied Mechanical Engineering and Renewable Energy, 2024)
The main problems in drying crackers are non-uniform drying and drying that still uses solar energy. During the rainy season, the process of drying crackers cannot be done quickly or takes a long time, thereby reducing the amount of cracker production in cracker MSMEs. Therefore, the solution that can be used is to use simple technology, a cracker drying oven machine, which can help the productivity of cracker small businesses in the drying process when the rainy season arrives. This research aims to determine the heat distribution in the cracker drying oven box using Computational Fluid Dynamics, determine the optimal temperature for drying crackers using a cracker drying oven machine and find out how long it takes to dry crackers using a cracker drying oven machine. From the simulation results using Ansys Fluent 19.2 software, it was found that the heat distribution was almost even in the drying box on each shelf with a heating source inlet of 75 ˚C with a temperature range of 49 ˚C - 54 ˚C on each shelf in stages. From the direct experimental results, it was found that the drying process with a heating source of 75 ˚C resulted in a decrease in the weight of crackers from the initial unit weight of 6 grams and the final unit weight of crackers of 3 grams. The drying process with a cracker drying oven machine lasts for 3 hours to achieve complete drying. Keywords: Cracker drying oven machine, heat distribution, computational fluid dynamics